Pekanbaru Trade Center Dengan Pendekatan Arsitektur Futuristik - Maulana, Sultan Jordansyah; Hidayat, Wahyu; Novan, Andre (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pekanbaru is the capital of Riau Province which became the center of industry and trade activity in Riau Province. However, Pekanbaru City currently does not yet have an appropriate facility to accommodate and manage the ever-increasing trade activities. Therefore, the purpose of this research is to design Pekanbaru Trade Center needed by Pekanbaru City to accommodate trading activities with facilities such as convention, exibition and retail, to facilitate and develop trade activities in Pekanbaru city. Research methods used through field survey, literature review, and analysis of Trade Center building. Pekanbaru Trade Center is designed with futuristic architectural themes emphasized on mass form with futuristic architectural features that are future-oriented concept and deconstruction shape. The concept used is mobility with the notion of easy to move or move. The result of this research shows that the Trade Center design applies futuristic theme on the shape and facade of the building by taking the form that is not constant like the use of circle pattern and curve for dynamic and flexible impression.Keywords: Architecture, Trade Center, Pekanbaru, Futuristic